2018
DOI: 10.1155/2018/5329386
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Antioxidant Activity and Quality Attributes of Yogurt Enhanced with Wild Herbs Extracts

Abstract: e milk and yogurt products assortment has expanded by their enhancement with herb extracts, bres extracted from byproducts of the fruit processing industry and also fresh spices. e aim of the present study was to test to what extent the addition of di erent herb extracts in yogurt will improve its qualitative characteristics and antioxidant activity. e aqueous extracts obtained from the four plants are considered in this study, respectively, thistle (Silybum marianum L.), hawthorn (Crataegus monogyna), sage (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
31
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 39 publications
(54 reference statements)
9
31
1
Order By: Relevance
“…Many authors have investigated the influence of different additives on the rheological parameters of yoghurts. Dabija et al [ 29 ], who evaluated yoghurts enriched with different herb extracts, also showed their lower viscosity values in comparison with the control sample. While El Said et al [ 13 ], evaluating yoghurts fortified with pomegranate peel extract, concluded that the increase of the additive concentration negatively influenced the viscosity, which was explained by its impact on the aggregation of the casein network in yoghurts via electrostatic interaction, and in the resistance of the yoghurt matrix to flow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have investigated the influence of different additives on the rheological parameters of yoghurts. Dabija et al [ 29 ], who evaluated yoghurts enriched with different herb extracts, also showed their lower viscosity values in comparison with the control sample. While El Said et al [ 13 ], evaluating yoghurts fortified with pomegranate peel extract, concluded that the increase of the additive concentration negatively influenced the viscosity, which was explained by its impact on the aggregation of the casein network in yoghurts via electrostatic interaction, and in the resistance of the yoghurt matrix to flow.…”
Section: Resultsmentioning
confidence: 99%
“…The maintenance of high antioxidant activity may also be a result of the presence in the products of other bioactive compounds such as peptides and amino acids, which also function as antioxidants. Many authors in their research have shown that the antioxidant activity of yoghurts is influenced by the kind and amount of polyphenolic additive [ 29 , 34 ]. Analyzing yoghurts enriched with the addition of 15% and 30% of strawberry pulp, Jaster et al [ 34 ] proved a significant elevation of antioxidant activity in those products.…”
Section: Resultsmentioning
confidence: 99%
“…Yogurt is one of the most commonly used fermented milk products that has received special attention due to its proven health features [1].…”
Section: Introductionmentioning
confidence: 99%
“…* Yogurt is an important source of bioactive peptides which are formed during fermentation, but generally has limited antioxidant activity. For this reason, in recent times, it's a great interest to produce yogurt with natural antioxidants [3]. Bioactive food components have multiple beneficial effects on many diseases and are usually found in multiple forms such as glycosylated, esterified, thiolated or hydroxylated [2].…”
Section: Introductionmentioning
confidence: 99%
“…Herbal nutraceuticals are an alternative for people who want to prevent and treat certain diseases. Therefore, in the recent past, it has been an increase in the demand for herbal medicines in various food products, especially in yogurt [3]. Basil (Ocimum basilicum L.) is part of the Lamiaceae family and is widely used in culinary art.…”
Section: Introductionmentioning
confidence: 99%